Resisting Culinary Nationalism: Dalit Counter-Cuisines in the Life Narratives of Urmila Pawar and Baby Kamble - James, Chithira; Mathew, Reju George (SARE: Southeast Asian Review of English, 2023)
Culinary nationalism in India has given rise to a hegemony of vegetarianism, excluding numerous regional and ethnic cuisines in the process. A homogeneous culinary identity is attempted by othering specific communities like Christians and Muslims, lower caste Hindus, and tribal groups, disputing the legitimacy of their national belonging and, hence, their culinary traditions. The traditional gender roles of women in kitchen spaces, along with their higher vulnerability to food insecurity, make food a prominent motif in Dalit women’s writing. This paper analyses how Dalit culinary practices, as recounted in the life narratives of Urmila Pawar and Baby Kamble, contest and redefine culinary nationalism and subvert the notion of ritual pollution or purity. Pawar’s The Weave of My Life and Kamble’s The Prisons We Broke detail the everyday practices of Dalit women, particularly those concerning food, as resistance to ethno-religious nationalism. Using Michel de Certeau’s theorization of everyday life, the paper reads the everyday practices of Dalit women as tactics that resist the strategies of Hindu/cultural nationalism. By depicting a carnival of the silenced Dalit cuisines as counter-cuisines and documenting the recipes of the same, these literary works assert Dalit culinary identities and provide a site for contestation of right-wing culinary hegemony. Keywords: Culinary nationalism, Cooking, Food, Ritual pollution, Tactics, Strategy